PENGARUH CASH RATIO, DEBT TO ASET RATIO, UKURAN PERUSAHAAN, DAN INVENTORY TURNOVER TERHADAP RETURN ON ASET - Maliny Putry Widowati; Ivo Rolanda (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This research is motivated by the importance of a company's ability to manage financial performance to increase profitability, especially in pharmaceutical sub-sector companies that face high competition and industry dynamics, especially in the post-pandemic period characterized by fluctuating financial performance. This study aims to analyze the effect of Cash Ratio, Debt to Asset Ratio, Company Size, and Inventory Turnover on Return on Assets in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the period 2019-2024. This study uses a quantitative research method with secondary data in the form of company financial reports obtained from the Indonesia Stock Exchange. The sampling technique used is Census Sampling, namely the entire population is used as a research sample. The data analysis method used is Multiple Linear Regression Analysis with the help of the IBM SPSS program version 26. The results show that Cash Ratio has a positive effect on Return on Assets, Debt to Asset Ratio and Company Size have a negative effect on Return on Assets, while Inventory Turnover has no effect on Return on Assets.